Advocacy and Social Justice Approaches With Immigrants and Refugees in Counsellor Education - Snow, Kevin C.; Harrichand, John J. S.; Mwendwa, Joy M. (Canadian Journal of Counselling and Psychotherapy, 2021)
In the current world, working with immigrants and refugees presents unique clinical and case management challenges that may go beyond standard training offered in most counsellor education courses on diversity. This applied conceptual article examines some of the barriers to working with immigrants and refugees. It also discusses approaches to including a focus on immigrants and refugees in counsellor education programs and courses as well as suggestions for counsellors working with these members of the community. In addition, an advocacy and social justice mandate to provide exposure to and teaching about clinical work with these often overlooked members of society is presented.